A Comparative Study on the Reception of AI-Generated and Human-Written Flash Fiction by the Students of the English Literature Study Program - Maya Kurnia Dewi; Ratih Laily Nurjanah; Deswandito Dwi Saptanto; Adam Zidan Fahrezi; Irene Sharon Margaretha (Universitas Dian Nuswantoro, 2025)
The emergence of generative artificial intelligence (AI) fundamentally challenges traditional literary paradigms that burden the modern reader with authenticating the text's source. This study empirically investigates the reception of AI-generated flash fiction (Text A) and human-written flash fiction (Text B) by 16 4th Semester English Literature students at Universitas Ngudi Waluyo. The research utilizes a mixed-methods approach grounded in Hans Robert Jauss’s reception theory, particularly the concept of the horizon of expectations. The core research methodology employs a